Low Functional β-Diversity Despite High Taxonomic β-Diversity among Tropical Estuarine Fish Communities - Villéger, Sébastien; Miranda, Julia Ramos; Hernandez, Domingo Flores; Mouillot, David (PLOS ONE, 2012)
The concept of β-diversity, defined as dissimilarity among communities, has been widely used to investigate biodiversity patterns and community assembly rules. However, in ecosystems with high taxonomic β-diversity, due to marked environmental gradients, the level of functional β-diversity among communities is largely overlooked while it may reveal processes shaping community structure. Here, decomposing biodiversity indices into α (local) and γ (regional) components, we estimated taxonomic and functional β-diversity among tropical estuarine fish communities, through space and time. We found extremely low functional β-diversity values among fish communities (<1.5%) despite high dissimilarity in species composition and species dominance. Additionally, in contrast to the high α and γ taxonomic diversities, α and γ functional diversities were very close to the minimal value. These patterns were caused by two dominant functional groups which maintained a similar functional structure over space and time, despite the strong dissimilarity in taxonomic structure along environmental gradients. Our findings suggest that taxonomic and functional β-diversity deserve to be quantified simultaneously since these two facets can show contrasting patterns and the differences can in turn shed light on community assembly rules.